Carbon coated core–shell multifunctional fluorescent SPIONs. Issue 22 (30th May 2018) - Tiwari, Ashish; Verma, Navneet C.; Singh, Anup; Nandi, Chayan K.; Randhawa, Jaspreet K.
Abstract : A novel one step method to synthesize non-toxic carbon coated highly photostable core–shell magnetic and fluorescent SPIONs with long-lasting fluorescence alongside a superior magnetic resonance (MR) imaging ability. Abstract : Due to their unique magnetic properties, multiple surface functionality and biocompatibility, superparamagnetic iron oxide nanoparticles (SPIONs) show very promising characteristics as magnetic resonance (MR) contrast agents in biomedical applications. However, a lack of fluorescence makes SPIONs inappropriate for multimodal bioimaging. SPIONs surface functionalized by either organic fluorescent molecules or semiconductor quantum dots (QDs) have been reported as bioimaging probes but subsequent deterioration of the fluorescent dyes due to low photostability and quick photobleaching limits their long term practical application. In addition, QDs are found to be toxic in nature. Here, we present a novel one step method to synthesize non-toxic carbon coated highly photostable core–shell magnetic and fluorescent SPIONs with long-lasting fluorescence alongside a superior magnetic resonance (MR) imaging ability. Apart from the highly comparable superparamagnetic properties of the SPIONs, the optical response of the material is much better than commonly used Rhodamine or cyanine dyes.